Um Estudo sobre Raízes de Equações no Ensino Básico: Aplicando Teorias Numéricas através de Planilhas Eletrônicas - Majoni Neto, João (2021)
Historically, mathematics has always walked hand in hand with the development of humanity, ranging from the simple task of counting to the technological resources we have today. For this reason, the new educational guidelines, organized by the “Common National Curriculum Base (CNCB)”, bring as one of the specific competences of mathematics “Use mathematical processes and tools, including available digital technologies, to model and solve everyday, social and other knowledge issues, validating strategies and results.”. Based on this relationship, this work was developed to show how part of these technologies, in particular electronic spreadsheets, can be used to study the equations of conventional methods for basic education, through the principles of numerical calculus. For this undertaking, we will first make a brief analysis of the path of educational guidelines, and how they treated the teaching of mathematics. Then, we will look at a small part of the history of mathematics, focusing on the advancement of studies on numbers, on equations and on numerical methods of approximation. Then, we will talk about the teaching of numerical sets and equations in basic education, making in sequence the definition of real number. Before introducing numerical methods, we will give a brief presentation about electronic spreadsheets, showing their structure, commands, and functions necessary for their application. Ending with the suggestions for use, from the 8th year of Elementary School II, until the 3rd year of High School.